An Examination of Eye Conditions Associated with Retinal Vein Occlusion - Narawade, Vikrant (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Retinal vein occlusion (RVO) is a significant retinal vascular disorder that impacts the blood flow in the retina, leading to a range of visual and systemic complications. RVO is classified into three main types based on the location of the occlusion: Branch Retinal Vein Occlusion (BRVO), Central Retinal Vein Occlusion (CRVO), and Hemiretinal Vein Occlusion (HRVO). Each type has distinct clinical features, risk factors, and implications for vision and treatment. The high incidence of macular edema and severe visual impairment underscores the need for effective management strategies, including anti-VEGF therapy, corticosteroids, and laser treatment. The findings highlight the importance of personalized treatment plans tailored to the specific type and severity of RVO and its complications. The study reinforces the critical role of managing systemic risk factors such as hypertension, diabetes, and hyperlipidemia. Regular monitoring and control of these conditions are essential to prevent or mitigate the severity of RVO. The study’s observational design limits its ability to establish causality. Additionally, the sample sizes for some RVO types, particularly HRVO, are relatively small, which may affect the generalizability of the findings. Aim: The primary aim of this study is to evaluate the prevalence, clinical features, and visual outcomes of various ocular conditions associated with retinal vein occlusion (RVO). Material and Method: This prospective, observational cohort study was conducted in the ophthalmology department with 80 participants diagnosed with RVO. Each participant provided written informed consent. Comprehensive eye examinations were performed, including visual acuity testing, fundoscopic examination, intraocular pressure measurement, optical coherence tomography (OCT), fluorescein angiography, and fundus photography. Systemic parameters such as blood pressure, blood glucose levels, and lipid profiles were recorded to assess risk factors. Ocular complications such as macular edema, vitreous hemorrhage, neo-vascularization, and disc neo-vascularization were documented. Visual acuity was categorized into three groups: >6/18, 6/18–6/60, and <6/60. Results: BRVO was primarily associated with macular edema (16.2%), with 33.7% of patients exhibiting severe visual impairment (visual acuity <6/60). CRVO showed a broader range of complications, including vitreous hemorrhage (18.75%), macular edema (10%), neo-vascularization (5%), and disc neo-vascularization (6.2%). Approximately 21.2% of CRVO patients had severe visual impairment. HRVO had fewer complications, primarily vitreous hemorrhage (2.5%), with 7.5% of patients experiencing severe visual impairment. The highest prevalence of RVO was observed in the 61-70 years age group (37.5%), with a slightly higher incidence in females compared to males. BRVO and CRVO have higher proportions of patients with severe visual impairment compared to HRVO. HRVO has the lowest percentage of patients with severe visual impairment but also the lowest overall number of patients. Most of the patients with RVO experience significant visual impairment, with only a small percentage maintaining good visual acuity.